Stock Price Crash Risk Against Busyness with ESG Value as Moderating Variable: Evidence from Indonesia - Nadhief Fadlurrahman; Cynthia Afriani Utama (LPPM Universitas PGRI Sumatera Barat, 2025)
This study focuses on Stock Price Downside Risk (SPCR) and Stock Price Trends with ESG as a moderator in several companies listed on the Indonesia Stock Exchange. This study aims to bridge the existing knowledge gap in this field, where few studies have addressed the moderating effect of ESG on activity in Indonesia. This study collected samples from the Indonesia Stock Exchange between 2017 and 2024 and used System GMM as an instrument. This technique avoids the problems of endogeneity of regressors and unobserved heterogeneity while improving model efficiency. The results show that Stock Price Downside Risk (DUVOL) affects SPCR, while ESG is not statistically significant in decreasing or increasing SPCR. The conclusion of this study is to determine whether ESG as a moderating variable for Activity can predict SPCR. Both proxies failed to show that ESG is statistically significant in moderating Activity in predicting SPCR. The novelty of this study is several important points and steps that researchers might want to take in the future. First, try to divide ESG into three different pillars; E, S, and G to enrich the data and collect more relevant information for each observation point.